2013
DOI: 10.1128/jvi.02198-13
|View full text |Cite
|
Sign up to set email alerts
|

Prohibitin Interacts with Envelope Proteins of White Spot Syndrome Virus and Prevents Infection in the Red Swamp Crayfish, Procambarus clarkii

Abstract: b Prohibitins (PHBs) are ubiquitously expressed conserved proteins in eukaryotes that are associated with apoptosis, cancer formation, aging, stress responses, cell proliferation, and immune regulation. However, the function of PHBs in crustacean immunity remains largely unknown. In the present study, we identified a PHB in Procambarus clarkii red swamp crayfish, which was designated PcPHB1. PcPHB1 was widely distributed in several tissues, and its expression was significantly upregulated by white spot syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…VP19, VP24, VP26 and VP28 are the four major envelope proteins of WSSV and function in virus entry and systemic infection [3840]. VP24, VP26 and VP28 share high sequence homology with each other; however, VP19 has a unique structure and biological character [41, 42]. The CCP domain exists mainly in complement system proteins and promotes the formation of oligomers [43].…”
Section: Discussionmentioning
confidence: 99%
“…VP19, VP24, VP26 and VP28 are the four major envelope proteins of WSSV and function in virus entry and systemic infection [3840]. VP24, VP26 and VP28 share high sequence homology with each other; however, VP19 has a unique structure and biological character [41, 42]. The CCP domain exists mainly in complement system proteins and promotes the formation of oligomers [43].…”
Section: Discussionmentioning
confidence: 99%
“…The principle envelope proteins of WSSV, viral protein 28 (VP28) and VP19, play important roles in virus entry and systemic infection (9,10). Although some molecules from crustaceans were shown to be involved in virus infection or antiviral responses (11)(12)(13)(14), how WSSV is recognized by the host and how the virions enter the cells remain largely unknown. Thus, identification of critical factors during WSSV infection, especially the early viral entry stage, would be of great help in understanding the virus-host interaction and discovering the targets for disease control and prevention.…”
mentioning
confidence: 99%
“…Further study found that Litopenaeus vannamei AK (LvAK) interacted with VP14 in WSSV-infected shrimp and was beneficial for WSSV proliferation (21). Structural envelope proteins of viruses, which are the first components to come into contact with host cells (30), have been reported to have crucial roles in the entrance of viruses into host cells (31,32). VP19, VP24, VP26, and VP28 are the four major WSSV structural proteins and have been found to play key roles in WSSV infection (32).…”
Section: Discussionmentioning
confidence: 99%
“…Structural envelope proteins of viruses, which are the first components to come into contact with host cells (30), have been reported to have crucial roles in the entrance of viruses into host cells (31,32). VP19, VP24, VP26, and VP28 are the four major WSSV structural proteins and have been found to play key roles in WSSV infection (32). Therefore, we performed pulldown assays of MjAK with these WSSV envelope proteins and found that MjAK interacts with WSSV VP26 but not with VP14.…”
Section: Discussionmentioning
confidence: 99%